Language Acquisition in Early Childhood: Exploring Sentence Structures in a Child Raised by a Working Mother (e-Journal of Linguistics, 2025)
Language acquisition is a process of absorption and mastery of language that occurs naturally in children. During the developmental period of language acquisition, children require beneficial stimulation to optimally develop their language skills. Typically, this stimulation comes from parents, who are their closest caregivers. This research focuses on language acquisition in a 3-year-old child cared for by working mothers. It aims to identify and describe the types of sentence structures acquired and mastered by the child, as well as the factors influencing the child's first language acquisition, particularly in relation to parenting styles from a working mother’s perspective. The study employs a qualitative-descriptive method. The subject of the study is a female child aged 3 years and 6 months. The data required includes primary data obtained from observations and secondary data collected from interviews with individuals living in the child’s family environment and among neighbors. The results show that the research subject, Claudia (a pseudonym), who is 3 years and 6 months old, has mastered four types of sentence structures: declarative, interrogative, imperative, and exclamatory. Although the structures of these sentence modes are not perfect, Claudia's performance in producing them at her age is quite commendable. The observations and interviews reveal three main factors contributing to her speaking skills: social and family environmental factors, cognitive intelligence, and motivational factors.
Keywords: Language Acquisition; Early Childhood; Sentence Structures; Working Mother